Efficacy and safety of vedolizumab in elderly patients with inflammatory bowel disease: a matched case–control study. (17th September 2019) - Shashi, Preeti; Gopalakrishnan, Dharmesh; Parikh, Malav P; Shen, Bo; Kochhar, Gursimran
Abstract: Background: Vedolizumab was demonstrated to be safe and effective in adults with moderately to severely active inflammatory bowel disease (IBD) in clinical trials. However, there are limited data regarding its efficacy and safety in elderly patients. Methods: This was a case–control study comparing the efficacy (measured by rates of mucosal healing and need for IBD surgery) and safety of vedolizumab in IBD among patients ≥65 years of age (the elderly group) vs those <65 years (the control group). The two groups were matched individually on a 1:4 ratio based on gender and type of IBD. Conditional logistic regression was used for stratified analysis to calculate odds ratios and confidence intervals. Results: We included 25 IBD patients in the elderly group and 100 matched patients in the comparison group. Eighty patients had Crohn's disease and 45 had ulcerative colitis. At baseline, the groups were comparable with regard to duration of IBD, prior anti-TNF therapy, and prior IBD surgery. The rate of mucosal healing on follow-up endoscopy was comparable between the elderly and control groups (50% vs 53%, P = 0.507). Although more patients in the elderly group required IBD-related surgery while on vedolizumab, the difference did not reach statistical significance (40% vs 19%, P = 0.282). Rates of vedolizumab-related adverse effects—rash, arthralgia, infections, infusion reactions, and dyspnea—were comparable between the two groups (all P > 0.05). Conclusions: In a real-world setting, vedolizumab was demonstrated to have an efficacy and safety profile among elderly IBD patients that were comparable to younger controls.